AAGBS annual report 2021: staff - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2021)
Information about AAGBS staff and academic staff as well as appreciation speeches, retirement, welcoming newly reporting, congratulations on staff promotion, congratulations on staff appointment, and finally congratulations on staff achievement.